The sanitization of the farmers in the hygienics discusses in the 1910s - Pedro de Oliveira Milagres; Anderson da Cunha Baía (Universidade Federal do Norte do Tocantins, 2023)
We aimed to understand the hygienist discourse aimed at the Brazilian rural and agricultural spaces amid the rise of the sanitation movement in the backlands. To this end, we conducted an external analysis of the discourses produced by Belisário Pena, in his two main publications of expression in the sanitation movement, in articulation with the ideas of Monteiro Lobato and Alberto Torres. Based on the expeditions through the backlands, Pena characterized a sick sanitary picture in the Brazilian countryside and put it in circulation with a messianic appeal for hygiene. The debates within the intelligentsia of the time favored the hygienist discourses, linking up with the thought of Torres and Lobato to approach the rural and agricultural production spaces. As for Lobato, Pena influenced the writer's view, and, on the other hand, his discourses were favored by the representations of rural backwardness conveyed by the literary debate. Finally, it is considered that the discourse invested by Pena highlighted the diseases and the physical precariousness of rural and agricultural workers in the hygienic debate of the 1910s, and reinforced the State's responsibility for guaranteeing hygiene in these spaces.